THE IMPORTANCE OF INCLUSIVE EDUCATION IN SOLVING THE PROBLEM OF EQUALITY IN THE EDUCATION OF CHILDREN WITH SPECIAL NEEDS - Rakhimova Khurshidakhon Sadikovna; Oppoqxo‘jayev Xojixuja Azimjon o‘g‘li (Zeta Repository, 2023)
This article reflects the inclusion of children with disabilities in the process of inclusive education, the obstacles and difficulties faced by the industry in the introduction of inclusive education, and the achievements of the introduction of inclusive education.